PROTEINS AND SATIETY STRATEGIES (International Seven Journal of Multidisciplinary, 2021)
Protein plays a central role in regulating satiety and is considered one of the most effective macronutrients for appetite control and weight management. Its effects are mediated through multiple physiological mechanisms, including stimulation of anorexigenic hormones, delayed gastric emptying, and increased thermogenesis. These processes contribute to enhanced fullness, reduced subsequent energy intake, and improved dietary adherence. The quality and source of protein, whether animal or plant-based, influence satiety outcomes, while the timing and distribution of protein across meals, particularly breakfast, further optimize appetite regulation. Despite its benefits, high-protein diets must be carefully balanced to prevent excessive intake of saturated fat and to ensure long-term safety, especially in populations with specific health conditions. Understanding protein’s unique role in satiety provides valuable insights for the development of nutritional strategies aimed at weight management, obesity prevention, and overall health improvement.